Modelling the Impact of Migration on Government Expenditures in Spain, Italy, and France - Zatonatska, Tetiana; Forostiana, Yulia; Fareniuk, Yana; Zatonatskiy, Dmytro (Ekonomika, 2026)
Migration processes are one of the key social-economic challenges within the European Union (EU). This article aims to analyse and model the impact of migration and macroeconomic factors on government expenditures in major EU destination countries, such as Spain, Italy, and France by using regression models. It examines the influence of these factors on the total government spending and its components, such as social support, education, and healthcare for the period from 2000 to 2023. Migration factors include the number of immigrants and emigrants, share of employed migrants, housing-burdened migrants, and educational levels. Macroeconomic factors include GDP per capita, human development index (HDI), life expectancy, inflation, and foreign investment.The key findings reveal nonlinear relationships between government expenditures and analysed factors. GDP per capita, life expectancy, and HDI demonstrate strong positive impacts. Among the migration factors, the housing burden and low educational attainment were found to significantly increase spending, while higher migrant employment was found to reduce social costs. Based on the modelling results, governments should focus on training programmes for migrants, employer tax incentives, inflation-adjusted healthcare budgeting, and dedicated migration impact funds. The results provide empirical evidence for optimising migration integration strategies and budget planning in EU countries.